Erroneously Disgusted: fMRI Study Supports Disgust-Related Neural Reuse in Obsessive-Compulsive Disorder (OCD) - Viol, Kathrin; Aas, Benjamin; Kastinger, Anna; Kronbichler, Martin; Schöller, Helmut Johannes; Reiter, Eva-Maria; Said-Yürekli, Sarah; Kronbichler, Lisa; Kravanja-Spannberger, Brigitte; Stöger-Schmidinger, Barbara; Aichhorn, Wolfgang; Schiepek, Guenter Karl (Frontiers in Behavioral Neuroscience, 2019)
Objective fMRI scans of patients with Obsessive-Compulsive Disorder (OCD) consistently show a hyperactivity of the insular cortex, a region responsible for disgust-processing, when confronted with symptom-triggering stimuli. This asks for an investigation of the role of disgust and the insula in OCD patients. Methods 17 inpatients with OCD and 17 healthy controls underwent fMRI scanning. Whole-brain contrasts were calculated for “Disgust vs. Neutral” for both groups, plus an ANOVA to assess the interaction between group and condition. Additionally, the emotional dimensions of valence and arousal, along with the ability to cope, were assessed by picture ratings. Results The picture ratings confirmed the patients’ heightened sensitivity to disgust with higher values for arousal and inability to cope, but not for valence. fMRI scans revealed no hyperactivity of the insula in patients compared to controls for the condition “Disgust vs. Neutral”, indicating no basic hypersensitivity to disgusting stimuli. Increased activity in the precuneus in controls for this condition might correspond to the downregulation of arousal. Conclusions The absent differences in neural activity of the insula in patients compared to controls for the disgust-condition, but heightened activity for symptom-provoking conditions, suggest that the illness is due to an erroneous recruitment of the insula cortex for OCD-stimuli. The finding is interpreted within the framework of the neural reuse hypothesis.